The Impact of COVID-19 on DTP3 Vaccination Coverage in Europe (2012–2023) - Ines Aguinaga-Ontoso; Sara Guillen-Aguinaga; Laura Guillen-Aguinaga; Rosa Alas-Brun; Miriam Guillen-Aguinaga; Luc Onambele; Enrique Aguinaga-Ontoso; Esperanza Rayón-Valpuesta; Francisco Guillen-Grima (Vaccines)
Background: The COVID-19 pandemic disrupted routine child immunization efforts, threatening to reverse progress in controlling vaccine-preventable diseases. Materials and Methods: We analyzed the impact of COVID-19 on DTP3 vaccination in Europe by comparing trends before and after the pandemic using time series data from 2000 to 2023. Employing joinpoint regression, chi-square tests, and segmented regression analysis, we assessed DTP3 vaccination trends and coverage changes. Results: The findings revealed significant regional disparities across Europe. Statistical models indicated reductions in DTP3 coverage in countries such as Ireland, Sweden, and Switzerland, whereas Ukraine and San Marino showed improvements. Conclusions: There are variations in the effect of COVID-19 on DTP3 coverage rates, indicating the need for targeted public health strategies to address vaccine hesitancy, logistical barriers, and systemic inequities.